1984
DOI: 10.1177/014272378400501404
|View full text |Cite
|
Sign up to set email alerts
|

Communicative gestures and early sign language acquisition

Abstract: The gestural (non-sign) communication and symbolic functioning of 13 children who were acquiring Amercian Sign Language as a first language were compared with existing data for children learning a spoken language. Two communicative gestures, Giving and Communicative Pointing, were the strongest gestural correlates of lexicon size for both spoken and sign languages. However, whereas first referential words typically appear after the onset of Giving and Pointing, the initial sign productions of the children in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…This process of relating language to familiar social routines is facilitated by the fact that a very high proportion of maternal speech relates to objects and activities on which the child is currently focusing attention. (See Harris, Jones & Grant 1983, 1984 More recently, and more controversially, it has been suggested that the rate of children's early language development can be influenced by the extent to which adult speech provides opportunities to relate linguistic input to a familiar nonverbal context. (See Barnes, Gutfreund, Satterly & Wells 1983 and Harris, Jones, Brookes & Grant 1986.)…”
Section: Introductionmentioning
confidence: 99%
“…This process of relating language to familiar social routines is facilitated by the fact that a very high proportion of maternal speech relates to objects and activities on which the child is currently focusing attention. (See Harris, Jones & Grant 1983, 1984 More recently, and more controversially, it has been suggested that the rate of children's early language development can be influenced by the extent to which adult speech provides opportunities to relate linguistic input to a familiar nonverbal context. (See Barnes, Gutfreund, Satterly & Wells 1983 and Harris, Jones, Brookes & Grant 1986.)…”
Section: Introductionmentioning
confidence: 99%
“…There are hearing children born to deaf mothers. These children are exposed to a high frequency of signing in their linguistic environment and as well as acquiring sign language; they also acquire spoken language earlier than norms (Bonvillian, Orlansky, Novack, & Folven, 1983;Folven, Bonvillian, & Orlansky, 1984;Holmes & Holmes, 1980;Orlansky & Bonvillian, 1984. This led researchers to question and to then empirically investigate whether or not hearing children, with hearing parents, would also benefit from being taught to gesture before they could speak.…”
mentioning
confidence: 99%
“…But it seems so often that animal communication is non-analogical and arbitrary. And although there are communicative gestures that develop in deaf children that are analogical, even in sign development, many gestures appear to be arbitrary (Folven, Bonvillian, & Orlansky, 1984/1985. I suspect that analogical expression via the body is rare in animal species outside great apes and cetaceans, although that is still a moot point (see Mitchell, 1994aMitchell, , 2002d.…”
Section: Iconicity and Apperceptionmentioning
confidence: 99%